ЕФЕКТИВНІСТЬ ЗАСТОСУВАННЯ БІОПРЕПАРАТУ БисолбиСан НА СВІТЛО-КАШТАНОВИХ ГРУНТАХ СУХОСТЕПОВОЇ ЗОНИ САРАТОВСЬКОГО ЗАВОЛЖЖЯ - Тарасенко , П.В.; Никифоров , В.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2007)
The results of research-productive experiments on evaluation of seed inoculation and treatment of grain cereals with biological preparation BisolbiSun in dry-steppe zone of Saratov Zavolzhja are represented. The moisturing effect under the use of this preparation was also established.